'Du er verdens beste pappa': affect in parent–child multilingual interactions. Issue 10 (26th November 2022) - Lomeu Gomes, Rafael
ABSTRACT: This article examines the affective dimension of the linguistic repertoire of multilingual families. Specifically, resulting from a three-year ethnographic project in Norway, this study sets out to better understand the role of affect in parent–child interactions as members of two Brazilian-Norwegian families draw on their multilingual linguistic repertoires in the ongoing construction of their familial ties. A discursive analytical approach was employed to examine audio-recordings made by one of the parents of each family (i.e. around 15 h of recordings in total). The analysis demonstrates how certain linguistic features (i.e. terms of endearment and the 'you are … '-format), combined with the use of the participants' multilingual repertoire, accomplish three interrelated social actions; they: (i) convey parental value-laden aspirations of child-rearing, (ii) position children according to expected social roles, and (iii) forge parent–child ties. These findings are supplemented with interview data, which serve to illustrate the role of home-external contexts in encouraging the parents to use Portuguese with their children in the home. Focusing on the affective dimension of parent–child interactions as they draw on their multilingual repertoires to construct familial bonds contributes to an underexplored area in family multilingualism studies.